Retraction Note: In vitro and in vivo responses of macrophages to magnesium-doped titanium - Bin Li (Nature Portfolio, 2021)
Editor's Note: this Article has been retracted; the Retraction Note is available at https://doi.org/10.1038/s41598-021-88664-z .